Andragogical Approach to the Quality and Effectiveness of Vocational Adults Training (A Retrospective Study) [In Bulgarian] - C. Katansky (University of Sofia, 2009)
The article describes the basic results of a study dealing with the problem of quality and effectiveness of vocational training of adults in Bulgaria. Why is it retrospective? Because the subject of study is previous author's andragogical investigations on the vocational qualification system, adults learners, training process and principals. The author uses the andragogigal methodology and results in order to develop a new approach to the problem and original definitions of vocational training quality and effectiveness.